STRENGTHENING COMMUNITY CAPACITY TO BOOST IMMUNITY DURING THE COVID-19 PANDEMIC - Bambang Aditya Nugraha Bambang Aditya Nugraha; Sulastini Sulastini; Sandra Pebrianti Sandra Pebrianti (Jurnal Pengabdian Masyarakat DEDIKASI, 2026)
Covid-19 is a disease caused by a corona virus that was first discovered in theprovince of Wuhan, the People's Republic of China and has become a globalpandemic. The virus attacks the respiratory system and causes mild disturbancesto death. The severity of the symptoms that appear is related to the state ofimmunity. The worse the immunity, the more susceptible to contracting Covid-19. In addition, individuals with poor immunity tend to experience severemanifestations of covid. Therefore, it is important to increase immunity duringthe Covid-19 pandemic. Efforts made to increase immunity include increasingcommunity capacity through community service activities in the form of awebinar entitled "Tips to Increase Immunity During a Pandemic". There is adifference in the average value of the pre-test (83.79) and post-test (96.21) afterthe activity. As many as 66.7% of participants considered that the activity wentvery well. Thus, the webinar that was held was useful in increasing communitycapacity in increasing immunity during the co-19 pandemic. It is hoped that thisactivity will continue to be carried out at different targets in order to reduce thespread and transmission of Covid-19.